Konseptualisasi Model Manajemen Layanan Bimbingan dan Konseling Berbasis Website di Sekolah - Lakadjo, Mohamad Awal; Dwinanto, Arif; Pautina, Mohamad Rizal; Siregar, Ilham Kahiri (Technocouns: Journal of Technology in Guidance and Counseling, 2025)
School counseling services in Indonesia continue to face challenges, including fragmented management, weak evaluation systems, and limited technology integration. This study aims to develop a conceptual model for a web-based management system for school counseling services that is integrated, evidence-based, and adaptive to the Indonesian educational context. The study employed a Comprehensive Literature Review (CLR) approach with thematic analysis of national and international literature. The findings identified eight major challenges in school counseling services, the need for a digital management system based on data and aligned with national regulations, and resulted in a framework consisting of five integrated service cycles. Scientifically, this research expands the theoretical development of web-based counseling service management systems with a contextualized local approach. Practically, the model provides a concrete solution to enhance the effectiveness, accountability, and sustainability of school counseling services in Indonesia, while accelerating the adoption of evidence-based practices in educational settings.